KEPASTIAN HUKUM BAGI WAJIB PAJAK YANG MENGIKUTI TAX AMNESTY JILID II MELALUI PENGUNGKAPAN HARTA SECARA SUKARELA - Muhammad Hidayat Sumarna; Khalimi Khalimi (Jurnal Ilmiah Global Education, 2022)
This study aims to discuss how the position of the Notice of Disclosure of Assets and the legal certainty of the certificate of disclosure of net assets which is the cause of the dispute between the Taxpayer and the Director General of Taxes, by using the theory of awareness of the taxpayer and the theory of legal certainty. The method used by this writer is normative juridical research which is supported by a statute approach, a conceptual approach, a case approach based on primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal material is obtained through studies or reviewing legislation and library research as well as decisions of the Tax Court and Decisions of the Supreme Court which the researchers then analyze by means of systematic interpretation. The results of this study indicate that the examination of extensification and intensification will eventually lead to a tax assessment letter, namely a letter stating that there is a shortage of the amount of tax debt that must be paid and even an investigation can also occur on the taxpayer. Guided by Article 12 paragraph (2) and paragraph (3) of the KUP Law stipulates that the amount of tax payable according to the notification letter submitted by the taxpayer is the amount of tax payable in accordance with the provisions of the tax laws and regulations and the Director General of Taxes determines the amount of tax to be paid. payable if the Director General of Taxes obtains evidence that the amount of tax payable according to the Tax Return is incorrect.